A systematic literature review and analysis of visual pollution - Gao, Hangyu; Abu Bakar, Shamsul; Maulan, Suhardi; Mohd Yusof, Mohd Johari; Mundher, Riyadh; Guo, Yu; Chen, Benxue (Multidisciplinary Digital Publishing Institute, 2024)
Rapid urbanization has introduced new pollution challenges, with visual pollution becoming particularly prominent. This type of pollution affects both the visual environment and public psychology, impairing aesthetic appreciation. Visual pollution extends beyond outdoor advertising, manifesting in various forms across urban, roadway, and natural areas. Although many studies have identified and analyzed visual pollution, there is still a lack of comprehensive knowledge and awareness of this problem. Until now, visual pollution has never been a unified and complete concept, definition, and research methodology. To address this gap, our systematic literature review examined existing literature to further explore and understand visual pollution. We systematically reviewed research articles published between 2008 and 2023, utilizing three journal databases: Web of Science, Scopus, and Google Scholar. Ultimately, 52 articles met the review criteria. The results of the study showed the types and characteristics of visual pollutants, the locations where visual pollution occurs, the various factors contributing to visual pollution, and the methodologies employed to study visual pollution. This study enhances professionals’ comprehension of visual pollution and its effects on the visual environment, equipping them to implement effective measures to reduce its impact and preserve visual quality in both urban and natural areas.